Editorial. Special issue on self-access writing support. - Rachael Ruegg (Studies in Self-Access Learning Journal, 2013)
This is a special issue on Self-Access Writing Support. Writing is a skill for which self direction is particularly important because it is so output oriented and as such is often such a solitary activity. Whether in the middle of a thriving Self-Access Centre, or at home alone in the middle of the night, writers need to know tools they can turn to for help, and need to understand how they can use those tools to best advantage.